Las Actitudes y prácticas en el cuidado domiciliario de pacientes con Sars Cov 2 en Sucumbios y Orellana: Attitudes and practices in the home care of patients with Sars Cov 2 Sucumbios and Orellana (La U Investiga, 2021)
The new SARS-CoV-2 coronavirus, affects to more than  5 million  people and represent a huge burden for the health systems around the world (1), more than 2,5 millions death and 117 millions of infected people worldwide (2). The research executed with the objective of identify the attitudes and practices of the population diagnosed with con Sars Cov2, quantitative design, non-experimental of an observational and descriptive type, non-probability convenience sampling, for convenience the total population of 355 people. The results achieved: middle age 30 years, female gender, mestiza ethnicity, single, and in common union, located in urban areas, high school level, occupation, public employees, farmers, students, and housewives; families conformed by 5 or 7 members, 1 or 2 rooms used it like a bedroom. The attitude of the patients and the caregivers was one of vulnerability to being exposed to this disease, they showed their mood changes, which increase the stress level to knowing the disease could get worse. The practices during the home isolation showed that the population is aware of vital signs and symptoms for a possible complication, they wear a surgical mask and when they cough or sneeze, they cover their nose and mouth, a few people change their mask when it gets wet or stained, beside to manipulation of the same without appropriate care, neither hand washing and alcohol disinfection; added a poor waste disposal. Ancestral medicine was used to counteract mild symptoms such as fever and cough, being eucalyptus and verbena more used as an infusion.  Key words: Sars Cov 2, attitude, practices, ancestral medicine, prevention, home treatment.
Keywords: Sars Cov 2, attitude, practices, ancestral medicine, prevention, home treatment.